Guía Metodológica docente para el proceso enseñanza aprendizaje de nociones Lógico - Matemáticas con niños y niñas de 3 años. - Torres Aguayo, Michelle Alejandra (2015)
The mathematical logic development is based on the constructivist perspective. That is why, the purpose of this Methodological guide is to design and Promote the knowledge of the mathematical logic on children under the age of three years. The development of mathematical logical thinking is achieved by stimulating curiosity in children, and uses recreational activities that allow the child to cycle through manipulation of the level of representation and then the expression with a suitable language. Therefore, in this methodological guide has been compiled several recreational activities that teachers can implement in the classroom. The type of activity, duration, materials needed and mechanics to realize it is specified.